Future teachers’ relationships with physical and technological environments - Pruneau, Diane; Kerry, Jackie; Freiman, Viktor; Langis, Joanne (European Journal of Sustainable Development, 2014)
Is future teachers’ contact with the physical environment significant enough for them to choose to educate their students about sustainability? These digital natives stand out from previous generations by their way of living, working and learning. Does the use of ICT by these young adults contribute to distancing them from the physical environment? Are future teachers, better informed thanks to technology, committed to environmental action? This research based on grounded theory was aimed at understanding future teachers’ relationships with physical and technological environments. The analysis of individual and group interviews with Moncton and Montreal teacher education students reveals that future teachers maintain a sporadic relation to the natural environment. They are still conscious that nature provides them with calmness, rejuvenation, and beauty. The Internet, visited at least two hours daily, offers them distraction, social affiliation, and personalized information, as well as facilitates their tasks and contact with the World. Future teachers are critical and cautious in their use of ICT, but are not much involved in the environmental cause. This research emphasizes the need to work on future teachers’ relationship to the physical environment with outdoor activities to get to know, appreciate, analyze, and improve the natural and urban environments. Key words: education, environment, Social networks,pedagogy.